Blockchain-Driven Digital Transformation in Coffee Industry: Business Model Canvas Implementation - Gumay, Wim Zembladimi; Cahyadi, Eko Ruddy; Muflikh, Yanti Nuraeni (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
PT. Alko Sumatra Kopi pioneered blockchain adoption in Indonesia to enhance supply chain traceability. This study analyzes the company’s business model transformation using the Business Model Canvas (BMC) framework. Data were collected through in-depth interviews, internal documents, and field observations. The analysis compares the nine BMC elements before and after blockchain implementation. Results show a shift in core activities toward digital recording, enhanced value propositions through traceability features, and strengthened customer trust. Customer segmentation transitioned from volume-based to value-based, targeting premium markets prioritizing ethics. Key resources evolved with digital infrastructure integration and trained personnel. This transformation improved operational efficiency and international competitiveness. The study proves strategically implemented blockchain can drive traditional agribusiness toward transparent, sustainable, and digitally integrated models.